(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Shyshkina K. M. The model of ensuring information security of children in primary school. The article deals with the problem of information security of children in secondary schools and the system of measures that are necessary to ensure it. The structural and functional models of information security of children at school online are reviewed.